PENCIPTAAN MOTIF BATIK SEBAGAI IKON KABUPATEN LUMAJANG - Marzuqi, Ahmad; Fianto, Achmad Yanu Alif; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Batik Indonesia is one of the works of the ancestral heritage of Indonesia. Batik art is the art of drawing on the fabric for clothing which became one of the cultural keluaga Indonesian kings of old. The development of batik motif with the character of an area is one of the potential development of a new motif (contemporary) through the development of regional motifs, almost all regions to develop the potential of batik owned. However, there are still some areas that are still in the stage of exploring the potential of batik to bring creativity and innovation strive to create unique on batik motifs, as well as a characteristic of their region. Lumajang is one of the areas that do not have an icon that symbolizes motif characteristic of the region. a lot of potential that can be developed in Lumajang to be iconic motif, such as from natural resources such as mountain semeru, semeru sand and the great banana. Therefore it is necessary for creation motif Lumajang accordance with local characteristics in an effort to promote local region Lumajang through media batik. Design done by observation, interviews, in-depth interviews, and literature studies using qualitative descriptive analysis and supported by the analysis of keyword searches to determine the design concepts used in the overall design. The concept of natural grandeur implemented on the icon motif Lumajang district. The concept of natural grandeur is a form of abundant natural resources that exist in Lumajang, this area has its own characteristics compared to other surrounding areas such as the results of the great banana plantations, namely, of the results of that sand mining and mountain tourism semeru. This concept was then applied to the creation of the motif as icons Lumajang.Â Keywords: Batik Pattern, Icon, Lumajang, The Greatest Of Nature